(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
جمعت عيّنات من المياه الجوفية من سبعة مواقع في حوض اللاذقية، خلال موسمي شتاء وصيف 2013 وقد عولجت العيّنات كيميائياً وإحصائياً بهدف تقييم نوعية وكيميائية المياه، بغرض تقييم صلاحيتها، وفهم الوضع الهيدروجيولوجي السائد. وقد لوحظ أن تراكيز العناصر الرئيسية المحددة يقع ضمن الحدود المسموح بها لمياه الشرب والري، كما تبين عدم وجود تغيرات حادة سواء بالملوحة أو النمط الجيوكيميائي للمياه باتجاه حركة المياه الجوفية.وأن المياه الجوفية في المواقع المختارة متأثرة بشكل كبير بالتركيب الليتولوجي لصخور الحامل المائي وهي عموماً غير ملوثة بالمياه البحرية باستثناء بئر المينا البيضا القريب من البحر، وهذا ما تم إثباته من خلال حساب بعض النسب الجيوكيميائية, كما أكدت هذه الدراسة أن الجريانات المائية في مختلف الحوامل المائية لحوض اللاذقية تملك علاقة هيدروليكية فيما بينها وبالتالي تشكل جرياناً مائياً واحداً ذا خصائص متجانسة في أغلب أجزائه, ويتطابق اتجاه حركة هذا الجريان في أكثر الأحيان مع الانحدار العام للمنطقة. Groundwater Samples were collected from seven locations distributed in Lattakiabasin during the winter and summer seasons of 2013.All samples were treated chemically and calculated statistically to evaluate the quality of the studied water and its chemical properties. The aim was to assess the suitability of the water to be potable and to determine the predominant hydrogeology status. It was noticed that the concentrations of the detected major elements were within allowed limits cited for drinking and irrigation waters. Also, it was found that there were no sharp changes either in salinity or in geochemical type of the water toward groundwater movement. Furthermore, the groundwater in the studied locations was largely influenced by lithological composition of aquatic holder. In general, these waters were found to be uncontaminated with marine waters with exception of the location called " wall of Al Mena Al Baida" that is located near the sea. This has been proven by calculation of some of geochemical proportions. Also, this study proved that the aquatic flows in the different water holders of Latakia basin have a hydrolytic relationship among them. Consequently, these flows comprise a uniform aquatic flow with homogenous properties in most of its parts. The direction movement of this uniform flow was identical to the general decline of the zone mostly.